Evaluation of the Fresh Properties of Cement Pastes: Part I-Response Models Applied to Changes in the One-Variable-at-a-Time Method - Lino Maia (2023)
The workability of cement-based materials is one of the features that makes these construction materials the most used worldwide. Measuring and understanding how cement-based constituent materials affect fresh properties depends on the experimental plans. The experimental plans deal with the constituent materials used, the tests carried out, and the run of experiments. Here, the fresh properties (workability) of cement-based pastes are evaluated based on the diameter in the mini-slump test and the time in the Marsh funnel test being measured. This overall study is composed of two parts. In Part I, tests were carried out on several cement-based paste compositions incorporating distinct constituent materials. The effects of the distinct constituent materials on the workability were analyzed. Furthermore, this work deals with an approach to the run of experiments. A typical run of experiments was applied, with basic sets of mixed compositions being studied by only changing one input parameter at a time. This approach used in Part I is faced with a more scientific approach applied in Part II of the work where, based on the design of experiments, multiple input parameters were changed at a time. This work showed that a basic run of experiments is quick and easy to apply and leads to results for simple analyses; conversely, it lacks information for advanced analyses and scientific conclusions. The tests carried out included studies on the effect on the workability caused by changes in the limestone filler content, the type of cement, the water-to-cement ratio, distinct superplasticizers, and shrinkage-reducing admixture.